ETIKA NATURAL TAOISME DAN KEMUNGKINAN PENERAPANNYA DI INDONESIA - Widisuseno, Iriyanto (Faculty of Humanities, Diponegoro University, 2011)
An ethical life in the perspective of Taoism is a life back to nature. Man must be able to understand how to relate to ethical meaning of the laws of nature and implement them in social relationship. This natural ethics of Taoism teaches that life must be equipped by virtue, which is a pure heart, sincerety, and willingness to care for the needs of fellow human beings. Taoist law of virtue contains universal values, thus make it important as an ethical consideration for Indonesian society which is experiencing a turbulent moral situation where morality is under-appreciated and a transitional political culture from the era of power-oriented bureaucracy to an era of democratic society advocating peopleâ€™s sovereignty. Â Keywords: taoism, natural ethics.